2021
DOI: 10.3847/1538-3881/ac1bb0
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Planetary Metastable Helium Absorption in the V1298 Tau System

Abstract: Early in their lives, planets endure extreme amounts of ionizing radiation from their host stars. For planets with primordial hydrogen and helium-rich envelopes, this can lead to substantial mass loss. Direct observations of atmospheric escape in young planetary systems can help elucidate this critical stage of planetary evolution. In this work, we search for metastable helium absorption—a tracer of tenuous gas in escaping atmospheres—during transits of three planets orbiting the young solar analog V1298 Tau. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…As part of this same study we also observed a transit of WASP-52b but did not detect a strong signal. We have since used this same observing mode to detect an atmopsheric outflow from HAT-P-18b (Paragas et al 2021) and found a tentative evidence for an outflow from the young planet V1298 Tau d (Vissapragada et al 2021).…”
Section: Ngts-5bmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of this same study we also observed a transit of WASP-52b but did not detect a strong signal. We have since used this same observing mode to detect an atmopsheric outflow from HAT-P-18b (Paragas et al 2021) and found a tentative evidence for an outflow from the young planet V1298 Tau d (Vissapragada et al 2021).…”
Section: Ngts-5bmentioning
confidence: 99%
“…All transits were observed in a custom metastable helium filter centered at 1083.3 nm with a full-width at half-maximum (FWHM) of 0.635 nm, previously introduced in Vissapragada et al (2020b). Each observation followed a similar sequence to that described in our previous papers (Vissapragada et al 2020b;Paragas et al 2021;Vissapragada et al 2021). We began each night by observing a helium arc lamp through the helium filter, allowing us to position the target star where the effective transmission function of the filter was centered on the helium feature.…”
Section: Palomar/wirc Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this same study, we also observed a transit of WASP-52b but did not detect a strong signal. We have since used this same observing mode to detect an atmospheric outflow from HAT-P-18b (Paragas et al 2021) and found tentative evidence for an outflow from the young planet V1298 Tau d (Vissapragada et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its size, such a cloud would have to be optical thin in the He I line. Vissapragada et al (2021), also report no detection of He I absorption in a narrow He I-band filter associated with transits of 'b' but do find tentative evidence for absorption associated with partials transits of 'd' on UT 2020 October 8 and November 27. The corresponding EW of their measurement is 0.027 ± 0.014 nm, which is consistent with our measurement of an ≈0.19 nm change during the September 26 transit.…”
Section: S U M M a Ry A N D Discussionmentioning
confidence: 88%